2017
DOI: 10.11648/j.jfa.20170501.11
|View full text |Cite
|
Sign up to set email alerts
|

Women Empowerment Through Microfinance: Empirical Evidence from Ghana

Abstract: Abstract:Microfinance programmes are currently promoted as a key strategy for simultaneously addressing both women empowerment and poverty alleviation in Ghana. However, there has been a hot debate on the potency of microfinance in empowering the Ghanaian women. Apparently, this research was conducted to analyse the impact of microfinance services on the economic and social empowerment of women in Ghana. A purposive non-probability sampling technique was utilized in a 500 sample-size selection of female microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
(43 reference statements)
3
32
0
Order By: Relevance
“…Thus, when women are empowered through micro-financing, the largely society stands to benefit. Addai (2017) found that most women depend on family and friends for financial support and that an increase in access to micro-finance will more likely increase the probability of women's economic and social empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when women are empowered through micro-financing, the largely society stands to benefit. Addai (2017) found that most women depend on family and friends for financial support and that an increase in access to micro-finance will more likely increase the probability of women's economic and social empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have tried to identify the main challenges faced by the clients of microfinance institutions (MFIs), and they usually come to a similar conclusion. According to Addai (2017) and Wulandari and Kassim (2016), one of the major challenges faced by clients of microfinance institutions is the issue of collaterals. Most clients of MFIs are unable to afford the collateral demanded by the MFIs especially if the clients demand higher amounts.…”
Section: Challenges Facing Clients Of Mfismentioning
confidence: 99%
“…The manifestation of the poor people that they can be reliable as bank customers is the supreme achievement of micro-financing. Microfinance has been an important tool for economic empowerment and poverty alleviation, especially in Africa, Asia, and other underdeveloped countries in other continents (Donou-Adonsou & Sylwester, 2016;Addai, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their involvement in intrahouse decisions is because of their matured relationship with spouse. Conversely, microcredit provides little progress in women's participation on major household purchase since micro loans improve the confidence of their spouses on them [16]. Irshad and Dr.Sathyadevi (2015), state that poverty eradication can be possible through microcredit support and improved knowledge of microcredit management.…”
Section: Literature Reviewmentioning
confidence: 99%